2011
DOI: 10.1159/000331588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Diagnostic and Therapeutic Approaches to Complications of Brucellosis: An Experience of 12 Years

Abstract: Objective: To describe the clinical presentations, laboratory findings, prevalence and pattern of complications and the response to treatment of brucellosis in a 12-year period in a Turkish research hospital. Materials and Methods: Between 1996 and 2008, 231 patients were diagnosed with brucellosis and treated in our clinic. Medical records of 189 of the 231 patients with at least one demonstrable complication of the disease were reviewed for anamnesis, diagnosis, complications, treatment and clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
(14 reference statements)
5
12
0
2
Order By: Relevance
“…[36] and Gur et al [17] reported higher ratios of osteoarticular involvement (68.1% and 69%, respectively) than we did in our study. Similar to our findings, Turan et al [37] and others reported 43.7% and 46.5% osteoarticular involvement, respectively [15,23]. In these studies, spondylodiscitis was the most frequent osteoarticular complication, similar to previous studies [15,22,23].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…[36] and Gur et al [17] reported higher ratios of osteoarticular involvement (68.1% and 69%, respectively) than we did in our study. Similar to our findings, Turan et al [37] and others reported 43.7% and 46.5% osteoarticular involvement, respectively [15,23]. In these studies, spondylodiscitis was the most frequent osteoarticular complication, similar to previous studies [15,22,23].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, Turan et al [37] and others reported 43.7% and 46.5% osteoarticular involvement, respectively [15,23]. In these studies, spondylodiscitis was the most frequent osteoarticular complication, similar to previous studies [15,22,23]. In some studies conducted in Turkey, however, sacroileitis or peripheric arthritis was found to be the most common form of osteoarticular involvement [17,37].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations